Socio-cultural barriers to youth voice in Nigerian school-based management committees: a multi-case analysis - Umar, Bashiru Bako; Krauss, Steven Eric; Ahrari, Seyedali; Abu Samah, Asnarulkhadi; Abdul Hamid, Jamaliah (Universiti Putra Malaysia Press, 2021)
This study explores the challenges of implementing youth voice in school-based management committees (SBMC) in Nigeria. SBMC are a form of youth-adult partnership that involve communities in the management of local primary schools. The program aims to provide community members, including vulnerable groups such as young people who traditionally lack a voice in community leadership structures, opportunities to partake in school governance. The current study used a qualitative case study approach by interviewing 19 committee members from two SBMCs in Niger State. Thematic analysis from interviews revealed that differential treatment of people of different ages, traditional power structures, the lack of a participatory culture in decision-making, and conventional role divisions impeded the practice of youth voice in the early stages of the SBMCs. The findings provide important insight from an understudied cultural setting on the need to consider sociocultural barriers to youth voice in community-based initiatives.